Designing Scalable Storage and Compute Platforms across On-Prem and Cloud - Vppalapati, Mallikarjun (International Journal of AI, BigData, Computational and Management Studies, 2026)
Establishing technologies is simplified for enterprises since operating systems may interface with several clouds. Organizations engage extensively in their own data centers, in addition to using public and private cloud infrastructures. This alteration significantly influences the construction, use, and modification of computers and data systems. One of IT’s objectives was to facilitate ease of manufacturing. It is now a crucial aspect of managing a firm that facilitates growth, ensures stability, and minimizes expenditures. Organizations must attend to management requirements while simultaneously enhancing their influence and capacity. This is due to the increasing size, complexity, and performance requirements of computer systems. Cloud-native systems are designed to develop and scale progressively. This may provide challenges for legacy or specialized systems that are only offered on-premises. To do this, we must consider power, latency, security, and data gravity. A platform that enables the storage, distribution, and management of data in many formats may not be user-friendly. This impedes the acquisition of new knowledge and progress. It also addresses the separation of the instruments that execute software programs from the programs themselves. Discussions are ongoing about the integration of standard planning, infrastructure-as-code, and policy-driven automation to monitor all scenarios throughout time and facilitate their development. The study indicated that job functions must be fragmented, data must be maintained current, processes must be accelerated, costs must be reduced, and hybrid and multi-cloud systems must operate well.